A bio-fabricated tesla valves and ultrasound waves-powered blood plasma viscometer - Chen, Wenqin; Xia, Mao; Zhu, Wentao; Xu, Zhiye; Cai, Bo; Shen, Han (Frontiers in Bioengineering and Biotechnology, 2024)
There is clinical evidence that the fresh blood viscosity is an important indicator in the development of vascular disorder and coagulation. However, existing clinical viscosity measurement techniques lack the ability to measure blood viscosity and replicate the in-vivo hemodynamics simultaneously. Here, we fabricate a novel digital device, called Tesla valves and ultrasound waves-powered blood plasma viscometer (TUBPV), that shows capacities in both viscosity measurement and coagulation monitoring. Based on the Hagen-Poiseuille equation, viscosity analysis can be faithfully performed by a video microscopy. Tesla-like channel ensured unidirectional liquid motion with stable pressure driven that was triggered by the interaction of Tesla valve structure and ultrasound waves. In few seconds the TUBPV can generate an accurate viscosity profile on clinic fresh blood samples from the flow time evaluation.Besides, Tesla-inspired microchannels can be used in the real-time coagulation monitoring. These results indicate that the TUBVP can serve as a point-of-care device in the ICU to evaluate the blood's viscosity and the anticoagulation treatment.